Analisis Implementasi Kebijakan Pengelolaan Sampah terhadap Perilaku Masyarakat Kelurahan Tegal Sari Mandala I Kecamatan Medan Denai - Bartolomeus Marulitua Simanjorang; Lestari Lumban Batu; Rouli Lumban Batu; Thereza Dwi Ningrum Siburian; Halking Halking (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
The waste problem in urban areas, including in Tegal Sari Mandala I Village, Medan Denai District, remains a serious issue. Although the government has established waste management policies through national and regional regulations, implementation on the ground often faces obstacles such as inadequate communication, limited resources, and low public awareness. This study aims to analyze the implementation of waste management policies and its impact on community behavior, based on public policy implementation theory, specifically George C. Edwards III’s model, which includes four key variables: communication, resources, disposition, and bureaucracy structure. Community behavior is analyzed through indicators such as waste disposal habits, compliance with rules, waste segregation, and participation in cleanliness activities. The research method used is a survey with a quantitative approach, involving 97 household heads in Tegal Sari Mandala I Village, selected through proportional random sampling. Data was collected through questionnaires, interviews, observations, and documentation. The analysis was conducted descriptively using descriptive data analysis and correlation tests to identify the relationship between policy implementation and community behavior. The findings show a significant relationship between the implementation of waste management policies and community behavior, with a Pearson correlation value of r = 0.709 and a significance level of 0.000. This indicates that better policy implementation leads to more positive community behavior in waste management, emphasizing the importance of improved policy communication, infrastructure strengthening, and coordination among relevant institutions.